Unveiling the radiological odyssey: Navigating the interstitial with artificial intelligence - Anna Russo; Vittorio Viglione; Linda Franzese; Vittorio Patanè; Tullio Valente; Fabio Perrotta; Alfonso Reginelli (Respirology Case Reports)
Abstract This study examines the radiological and clinical evolution of a case involving mixed idiopathic pulmonary fibrosis and chronic hypersensitivity pneumonitis, utilizing conventional CT imaging and artificial intelligence tool. Through a series of exams and clinical assessments, the patient was followed for over 3 years, highlighting the challenge in differentiating these interstitial pathologies and the importance of a multidisciplinary approach. The radiological progression towards pulmonary fibrosis was correlated with clinical symptoms, emphasizing the significance of early diagnosis and regular follow‐up. The combined use of advanced technologies offers a more comprehensive framework in managing complex lung diseases, enhancing the quality of care and understanding of interstitial pathologies.